2023
DOI: 10.1038/s41390-023-02555-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the perception of parents on children’s screentime: a systematic review and meta-synthesis of qualitative studies

Abstract: Background Screentime (ST) has been increasingly pervasive in young children. Evidence suggests positive and negative effects of ST on children’s development. Parents play a crucial role in influencing their children’s ST. There is limited research consolidating the parental perceptions related to children’s ST. This review consolidates the evidence on the perception of parents on their children’s ST. Methods Six electronic databases (PubMed, Embase, CINAHL, PsycINFO, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…The effects of ST on the development of children and adolescents have been identified by many research groups [6,9,44]. A team from Canada found that excessive ST has a negative impact on aspects of development [45], while other research findings [46] suggest that ST in children younger than 2 yo is associated with developmental delays, supporting the WHO guidelines.…”
Section: Developmentmentioning
confidence: 94%
See 2 more Smart Citations
“…The effects of ST on the development of children and adolescents have been identified by many research groups [6,9,44]. A team from Canada found that excessive ST has a negative impact on aspects of development [45], while other research findings [46] suggest that ST in children younger than 2 yo is associated with developmental delays, supporting the WHO guidelines.…”
Section: Developmentmentioning
confidence: 94%
“…This finding was moderated by the type of child-parent relationship, age, and country [55]. A review article by Chong SC et al studied what parents thought about their children's ST. Parents used DM as (i) a distraction for their children when they needed a break, (ii) an educational tool for their children (especially true for the interactive use of computers), and (iii) a reward or penalty system [44]. The last one has been documented as an RF for parentchild conflict [56].…”
Section: Child-parent Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from modelling the appropriate use of screens, parents can additionally prevent undesirable effects and encourage positive ones by choosing a quality content as well as by active mediation in the child's screen usage (Nathanson, 2001;Nichols, 2022;Skubic, 2018). Although the positive and negative effects of screen use on children's development have been established in several studies, there is a lack of research on the content children are exposed to on screens (Li et al, 2020), as well as on parents' perceptions of their children's screen exposure (Chong et al, 2023). As parents play a very important role in choosing the content viewed by young children, guiding them in the process of viewing and developing their healthy viewing habits (Ponti, 2023;Vintar Spreizter et al, 2021), our study focused on the perspective of parents.…”
Section: Introductionmentioning
confidence: 99%